2005
DOI: 10.1177/153537020523001107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Arterial Smooth Muscle Contraction: Focus on Rho

Abstract: The vascular smooth muscle cell is a highly specialized cell whose primary function is contraction and relaxation. It expresses a variety of contractile proteins, ion channels, and signalling molecules that regulate contraction. Upon contraction, vascular smooth muscle cells shorten, thereby decreasing the diameter of a blood vessel to regulate the blood flow and pressure. Contractile activity in vascular smooth muscle cells is initiated by a Ca(2+)-calmodulin interaction to stimulate phosphorylation of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 68 publications
1
72
1
2
Order By: Relevance
“…These studies have shown that G protein-coupled receptor agonists activate Rho-mediated signaling pathways that regulate MLC phosphorylation and tension generation. Extensive evidence from these studies indicates that RhoA can potentiate agonist-induced MLC phosphorylation by activating pathways that inhibit the catalytic activity of smooth muscle MLC phosphatase, and thereby enhance the Ca 2ϩ sensitivity of the contractile apparatus (19,47,53). However, the importance of RhoA-mediated signaling pathways in tension development in smooth muscle tissues contracted under physiologic conditions in which receptor-activated Ca 2ϩ signaling is maintained cannot be assessed from studies of permeabilized smooth muscle tissues.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies have shown that G protein-coupled receptor agonists activate Rho-mediated signaling pathways that regulate MLC phosphorylation and tension generation. Extensive evidence from these studies indicates that RhoA can potentiate agonist-induced MLC phosphorylation by activating pathways that inhibit the catalytic activity of smooth muscle MLC phosphatase, and thereby enhance the Ca 2ϩ sensitivity of the contractile apparatus (19,47,53). However, the importance of RhoA-mediated signaling pathways in tension development in smooth muscle tissues contracted under physiologic conditions in which receptor-activated Ca 2ϩ signaling is maintained cannot be assessed from studies of permeabilized smooth muscle tissues.…”
Section: Discussionmentioning
confidence: 93%
“…We conclude that the RhoA-mediated regulation of ACh-induced contractile tension in ASM results from its role in mediating actin polymerization rather than from effects on MLC phosphatase or MLC phosphorylation. cytoskeleton; calcium sensitization; myosin light chain phosphorylation; myosin light chain phosphatase; myosin phosphatase; calyculin A; myosin light chain kinase THE EFFECTS OF THE SMALL GTPase RhoA in regulating the Ca 2ϩ sensitivity of smooth muscle contraction are well documented and have been described for many smooth muscle tissue types, including airway smooth muscle (10,14,15,19,21,26,34,35,45,47,53). The effects of RhoA on the Ca 2ϩ sensitivity of contraction have been ascribed to its role in regulating the catalytic activity of smooth muscle myosin light chain (MLC) phosphatase (23,33,47,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Excitatory agonists, such as adrenergic agonists and contractile peptides like angiotensin II, can stimulate smooth muscle contraction through three distinct signaling pathways: Ca 2C influx through membrane Ca 2C channels, IP 3 -induced Ca 2C release from the sarcoplasmatic reticulum, and Ca 2C sensitizing mechanisms of the contractile machinery (Somlyo & Somlyo 1994, Hilgers & Webb 2005. The contraction-modulating effects of estrogens have been attributed to their Ca 2C antagonistic properties.…”
Section: Cmentioning
confidence: 99%
“…The ability to autophosphorylate (and activate, respectively) turns СaM KІІ into a somewhat Са 2+ -independent enzyme [25]. This makes it a potential candidate for phosphorylation and MLCK inactivation and initiation of tacrine-induced Са 2+ -independent relaxation [26]. Being a calmodulin antagonist, trifluoperazine inhibits СaM KІІ activity and the potential processes in which it is involved [27].…”
Section: Discussionmentioning
confidence: 99%